The relationship of the essential alpha-linolenic acid with heart rate variability in cross-country skiers - A. Yu. Lyudinina; A. L. Markov; E. R. Boyko (National Electronic Information Consortium (NEICON), 2020)
Objective: to examine the correlation between heart rate variability and plasma level of alpha-linolenic acid (ALA) in cross-country skiers. Materials and methods: the short-term heart rate variability (HRV) was examined in 19 high-trained male cross-country skiers from national team of the Komi Republic. The ECG recordings were analyzed using with the Ecosan-2007 complex. ALA analysis was performed on a gas chromatograph (Chromatek, Russia). Results: the plasma levels of ALA were positively associated with the relative value of high-frequency power and negatively correlated with the indices of centralization and vagosympathetic interaction and with absolute and relative values of low-frequency power. Conclusions: a lower plasma level of ALA in athletes was associated with the appearance of slow waves of higher orders, indicating a non-optimal level of regulation of heart rhythm.